2022
DOI: 10.1155/2022/6869730
|View full text |Cite
|
Sign up to set email alerts
|

Augmenter of Liver Regeneration (ALR) Protects Kidney from Ischemia/Reperfusion (I/R) Injury via Regulation of TLR4/MAPK Signaling Pathway

Abstract: Toll-like receptor 4 (TLR4) can mediate innate activation and inflammation, and it is typically expressed within the ischemic kidney. Augmenter of liver regeneration (ALR) acts as an immunoregulator with a high expression in the kidney induced by renal ischemia/reperfusion (I/R) injury. Exogenous ALR has indicated a role in protecting the kidney from I/R injury. The protective effect of ALR is due to the immune regulatory function which remains to be elucidated. In this study, rats induced by renal I/R were tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…augmenter of liver regeneration, carnitine palmitoyltransferase-1A, diabetic nephropathy, ferroptosis, lipid droplet-mitochondrial coupling, macrophage activation, mitochondria ferroptosis. 27 Intriguingly, Li et al 28 reported that ALR acts as an immunoregulator in the kidney after the induction of its high expression by renal I/R injury, and it decreases the infiltration of macrophage and the existence of inflammatory cytokines in I/R injury cell models through the TLR4/MAPK signaling pathway. These results imply that ALR could be a potential regulator of ferroptosis and macrophage activation in DN.…”
Section: Introductionmentioning
confidence: 99%
“…augmenter of liver regeneration, carnitine palmitoyltransferase-1A, diabetic nephropathy, ferroptosis, lipid droplet-mitochondrial coupling, macrophage activation, mitochondria ferroptosis. 27 Intriguingly, Li et al 28 reported that ALR acts as an immunoregulator in the kidney after the induction of its high expression by renal I/R injury, and it decreases the infiltration of macrophage and the existence of inflammatory cytokines in I/R injury cell models through the TLR4/MAPK signaling pathway. These results imply that ALR could be a potential regulator of ferroptosis and macrophage activation in DN.…”
Section: Introductionmentioning
confidence: 99%